Features of the spatiotemporal trend of grain and grain legumes yields in Polissia and Forest-Steppe zone of Ukraine - Зимароєва, А. А. (Scientific Progress & Innovations, 2018)
Currently, little is known about the spatial and temporal variability of grain and grain legumes yields patterns in Ukraine. The aim of this research was to characterize the spatial and temporal yields variability of grain and grain legumes grown in 155 administrative districts in Forest and Forest-Steppe zone of Ukraine over 27 years from 1991–2017. The analysis of the spatial and temporal dynamics of grain and legumes yields showed the complex nature of the processes that determine it. The common feature of temporal changes for all administrative districts is the existence of the trend that can be described by the fourth degree polynomial. We provide agroeconomic and agrotechnological origin to the nature of the trend. The yields dynamics of grain and grain legumes is described by the absolute term, which reflects the starting conditions of soil fertility in the initial period of research and the indicators of maximum rate of yields decline in the 90s and the maximum rate of yields increase in the 2000s. The indicators of the maximum rate of reduction and the maximum rate of increase of yields can be used as markers of agroecosystem stability to external factors. It can be noted that the Southern regions of Ukraine are less stable and more exposed to the destructive influence. And the Central and Western regions are more stable and rapidly increase productivity under favorable conditions. This research has found that the agroecological systems of the regions of Ukraine are far from the maximum ecological capacity, and agroeconomic and agrotechnological factors are the limiting now.